The Dentists' Understandings on Dental Medical Records in East Java, Indonesia - Kurniawan, Arofi; Chusida, An'nisaa; Marini, Maria Istiqomah; Rizky, Beta Novia; Roosyanto Prakoeswa, Beshlina Fitri Widayanti; Damayanti, Prasetyaning Astrid; Salsabila, Zhafira Nur Aini (Faculty of Dental Medicine Universitas Airlangga, 2021)
Introduction: A dental medical record is a systematic documentation of a patient, provided by the dentists. Various information including the patient data, diagnoses, treatments, and odontogram are recorded in the dental medical records. In Indonesia, the guideline of dental medical records has been established by the Ministry of Health. However, the preliminary study by the Department of Forensic Odontology, Faculty of Dental Medicine Universitas Airlangga, showed that many dentists documented the medical records, not following the Medical Record Guidelines from the Ministry of Health. Purpose: This study aims to determine the dentists' understandings of the completeness of dental medical records according to the Dental Medical Record Guidelines by the Ministry of Health of Indonesia. Methods: A total of 358 dentists in East Java participated in this study by fulfilling an online questionnaire. Results: The results showed that approximately 27.4% of the respondents are conducting dental medical records following Dental Medical Record Guidelines. Conclusion: The results of this study are expected to be considered as a reference for the implementation of socialization on the Dental Medical Record Guidelines and the formulation of policies that regulate the use of dental medical records following national standards.